Fish oil and vitamin D in pregnancy for the prevention of early childhood asthma: study protocol for two double-blinded, randomised controlled trials - Klaus Bønnelykke; Jakob Stokholm; Rebecca Vinding; Bo Chawes; Julie Nyholm Kyvsgaard; Ulrik Ralfkiaer; Marianne Mikkelsen; Nicklas Brustad; Sarah Brandt; Nilo Vahman (BMJ Open)
Introduction Previous randomised controlled trials (RCTs) have indicated a protective role of pregnancy supplementation with fish oil and high-dose vitamin D, respectively, on offspring asthma, infections and several other disorders in early childhood. However, current evidence is not considered sufficient for recommending these supplements in pregnancy. In two RCTs, we aim to investigate whether these protective effects can be confirmed in larger trials with the goal of changing clinical practice and improving child health.Methods and analysis Randomisation of 4000 pregnant women to either (1) (n=2000) the fish oil trial of 2.4 g/day (55% eicosapentaenoic acid (EPA) and 37% docosahexaenoic acid (DHA)) in triacylglycerol form versus placebo or (2) (n=2000) the vitamin D trial of high-dose (3200 IU/day) vitamin D versus placebo on top of the recommended 400 IU/day. Supplementation begins in gestational week 24 (22–26) until 1 week after delivery. Allocation to the trials will be determined based on the preinterventional maternal blood levels of EPA+DHA with a dried blood screening test. Women with low levels (below 4.7% of total fatty acids) will be assigned to the fish oil RCT, and women with high levels will be assigned to the vitamin D RCT. Maternal blood will be used for genetic, metabolomic and proteomic profiling. A 3-year follow-up of the children with longitudinal registration of parent-reported symptoms, diagnoses, medication use and hospitalisations will be performed. The primary outcome is persistent wheeze or asthma until age 3 years, with predefined analyses of effect modification by maternal genotypes. Secondary outcomes are lower respiratory tract infections, gastrointestinal infections, croup, troublesome lung symptoms, eczema, allergy, bone fractures, developmental milestones, mental health, cognition and growth until age 3 years. A follow-up on both primary and secondary outcomes is planned after unblinding, from age 3–6 years.Ethics and dissemination The RCTs are approved by the Danish local ethics committee (H-23055833). The studies are registered at ClinicalTrials.gov (NCT06560255 and NCT06570889). Study results will be communicated to the medical community, including publications in peer-reviewed journals. All results will be published and available on www.copsac.com.Trial registration number NCT06560255 and NCT06570889.